Urban renewal planning practice and form in early-modern Guangxi (1925-1936) - Ji, Li (International Planning History Society Proceedings, 2018)
Aiming at the old cities renovation planning practice by Guangxi Government with their military and political power from the 1920s to the 1930s, who were local warlords before and formed the New Kwai Clique ruling with Three People’s Principles and Material Development Planning under the guidance of Sun Zhongshan, the paper analyzes the evolution Characteristics of urban form in the four major cities, which was Wuzhou, Liuzhou, Nanning and Guilin, includes that demolishing the walls, constructing ring roads at the original sites, straightening streets of cities, expanding and changing them to roads, then building arcades on both sides to escape the rain and the sun, and finally adding the public facilities with drainage, docks, water and power supply, and so on, that could be considered as existed old city reconstruction with gradual developments. And it also shows that planning criss-cross roads network in a new district outside the old cities of the jumping rhythm by with new urban core. Either the former or the latter were both applying western planning theories for the purpose of improving and beautifying the urban environment. While presenting different urban forms, it could be sum up that the pattern went to the style “Streets City